PENGARUH PERSEPSI NASABAH ATAS RISIKO, KEPERCAYAAN, MANFAAT, DAN KEMUDAHAN PENGGUNAAN TERHADAP PENGGUNAAN INTERNET BANKING (Studi Empiris pada Nasabah Bank Umum di Kota Banda Aceh) - Muhammad Fadhil; Rudy Fachruddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The research examines the influence of Customers Perceived of Risk, Trust, Usefulnes, and Ease of Use on the use of Internet Banking. The results of this study are expected to contribute to the Banks in order to enhancement service programs that easier for its customers. The object of this study is the Banks customers in Banda Aceh city who use internet banking. samples were taken by purposive sampling method. There are 100 samples of the data that become the object to be researched. The results of this research show that simultaneous of Perceived of Risk, Trust, Usefulnes, and Ease of Use have effect on the use of Internet Banking. Partially the research shows that Perceived of Trust, Usefulnes, and Ease of Use have positive effect on the use of Internet Banking, and Perceived of Risk have negative effect on the use of Internet Banking. Keywords: Perceived of risk, trust, usefulness, ease of use, and the use of internet banking